Quantum chemical calculation of maximum absorption wavelength based on dispersed dye structure - Xuekun Xue; Lingling Hu; Yue Liu (Journal of Engineered Fibers and Fabrics)
The light absorption properties of dyes constitute a pivotal characteristic that significantly influences their performance and application. To investigate the relationship between the molecular structure of mono-azo orange series disperse dyes and their corresponding maximum absorption wavelengths, a predictive model was developed. Employing Gaussian quantum chemistry software, the relationship between the molecular structures of four mono-azo orange series disperse dyes and their respective maximum absorption wavelengths was systematically examined. In the present study, the initial conformations of selected disperse dye molecules were generated, followed by the optimization of the energy-minimized conformations using quantum chemical DFT. The thermal correction to free energy and single-point energy were computed to determine the Gibbs free energy and the Boltzmann distribution ratio at 298.15 K. Conformations exhibiting a Boltzmann distribution ratio of at least 5% were selected for subsequent excited-state calculations, which yielded the ultraviolet-visible absorption spectra and the corresponding maximum absorption wavelength. A fitting prediction model based on optimization for the maximum absorption wavelength was then established. The results demonstrate that when this model is applied to predict the maximum absorption wavelength of a single azo orange series disperse dye, the testing error rate remains within 6%, suggesting a high degree of consistency within an acceptable range of accuracy. These findings suggest that the model could serve as a valuable technical reference for predicting the absorption performance parameters of disperse dyes, thus contributing to the green innovation and sustainable development of these materials.